The aristocratic Constitution of Carthage and its democratic implications (Iter, 2022)
The article will focus on Aristotle’s classic definition of Aristocracy,analyzing the specific example of the city of Carthage and its aristocratic constitution, which was mentioned by Aristotle himself. The singularityof the political constitution of this North African city will be emphasized,becauseas it is an unknown case with certain special characteristics -whetherpositive or negative- for the study of antiquity, especially since Carthagedid not belong to the Greek cultural context. Nevertheless, this city and itsconstitution followed a similar course in political evolution comparable tothat of other Greek polis.
Keywords: Aristocracy - Oligarchy - Political Constitutions - Mercenaries - Citizenship - Republic